Meningkatkan Motivasi Bimbingan Belajar Siswa-Siswi SD Melalui Metode Ceramah dan Bermain Pada Masa Pandemi Covid-19 di Dusun Karang Nongko Desa Sumberagung Kecamatan Plosoklaten - Muchamad Machsun; Tasmin (LP3M IAIFA Kediri, 2021)
In general, tutoring is not an activity that takes up students' playing time, but tutoring is one of the alternative ways used to motivate students to study harder during the Covid-19 pandemic. It has been proven that tutoring can provide greater value to the learning process of students. Moreover, during the Covid-19 pandemic, students were getting very little education directly from their teachers, because they had to learn on their own from home online. In this case the author took the initiative to develop offline tutoring to help students explain the subject matter and help do the assignments from their teachers with discipline while complying with health protocols. In addition to guiding them to increase learning motivation during the Covid-19 pandemic, the author also gave a game or a questionnaire after tutoring to provide a comfortable, happy and less tense atmosphere in tutoring.